2022
DOI: 10.1002/jsfa.11980
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐hydrostatic pressure and high‐pressure homogenization on the biological activity of cabbage dietary fiber

Abstract: BACKGROUND: Cabbage is one of the most economical cooked vegetables in terms of its relatively low price and high nutritional value. It is rich in dietary fiber, multivitamins, and a variety of anti-oxidants. In this study, we compared the effects of high-hydrostatic pressure (HHP) and high-pressure homogenization (HPH) treatments on changes in composition and physiological functions of cabbage dietary fiber. RESULTS:The total dietary fiber content (36.06 ± 1.65%) and nitrite ion adsorption capacity (2.37 ± 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The IDF content of KP treated with HPP for 5 min at all pressures increased significantly ( P < 0.05), whereas the SDF content did not show any significant difference or even decreased. SDF is evenly distributed across the cell and comprises mainly oligosaccharides and pectin, whereas IDF is primarily located in the cell wall and comprises mainly cellulose, hemicellulose, and lignin ( Chen and Wu, 2022 ). A previous study demonstrated that some small-molecular-weight oligosaccharides may be lost during HPP treatment, leading to a decrease in SDF content ( Sang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The IDF content of KP treated with HPP for 5 min at all pressures increased significantly ( P < 0.05), whereas the SDF content did not show any significant difference or even decreased. SDF is evenly distributed across the cell and comprises mainly oligosaccharides and pectin, whereas IDF is primarily located in the cell wall and comprises mainly cellulose, hemicellulose, and lignin ( Chen and Wu, 2022 ). A previous study demonstrated that some small-molecular-weight oligosaccharides may be lost during HPP treatment, leading to a decrease in SDF content ( Sang et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have demonstrated that either SDF or IDF derived from L. japonica could alleviate chronic diseases such as diabetes and obesity in mice by increasing the abundance of beneficial bacteria (e.g., Akkermansia ) and decreasing the abundance of pernicious bacteria (e.g., Staphylococcus ) through fermentation, which produced short-chain fatty acids and lowered the pH ( Wang et al, 2022 ; Zhang et al, 2021 ). Although both SDF and IDF have many health benefits, SDF has shown more positive effects in increasing viscosity, forming gels, and providing better texture and taste and is generally considered more important than IDF ( Chen and Wu, 2022 ). However, IDF accounts for a large proportion of most plant-based foods, so the conversion of IDF to SDF by appropriate processing methods is imperative for the advancement of functional food products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some fibers from plant residues change their properties when subjected to shear forces, such as the passage through a high-pressure homogenizer, some types of mills, or ultraturrax [ 19 , 20 ]. In the case of citrus fiber, changes in its properties have also been observed after high-pressure homogenization, and/or ball mill [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%